PENGARUH NILAI KEBANGSAAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Ghaida Humairoh; Eko Ribawati (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aims to analyze the influence of national values on Indonesia's economic growth. The research is based on the importance of social values and national identity in maintaining social cohesion and strengthening economic resilience. The method used is a Systematic Literature Review with the PRISMA 2020 approach, reviewing 25 relevant scientific articles published between 2021 and 2025 from various databases. Thematic analysis was employed to identify the relationship between national values, social capital, economic nationalism, character education, and public policy on economic growth dynamics. The findings reveal that national values significantly act as social capital supporting socio-political stability, enhancing productive work ethics, and promoting economic independence through nationalism policies and inclusive economic movements such as gotong royong. These results confirm that strengthening national values is not only a moral aspect but also a strategic factor in Indonesia's sustainable economic development.